The Impact of Doctors' Social Identity on Patient Trust in Obstetrics and Gynecology: A Quasi-Experimental Study among Javanese Muslim Women: Peran Identitas Sosial Dokter terhadap Kepercayaan Pasien: Sebuah Eksperimen Kuasi - Apriliawati, Denisa; Anadyarisya, Megatiara; Fuadi, Ahmad Nur; Azizah, Aulia Afna Nurfitria; Thoha, Ahmad Johan Faidlony (Universitas Islam Indonesia, 2023)
Trust is an important factor for determining the quality of a professional doctor-patient relationship, particularly in the field of Obstetrics and Gynecology (Ob-Gyn), where it is essential for enhancing healthcare services for mothers and babies. Among the various factors influencing the level of trust patients have in medical personnel, their socio-demographic identity is considered very important. Therefore, this study aimed to investigate the influence of a doctor's social identity, including gender, religion, and race, on the level of trust reported by patients. A quasi-experimental design with a 2 × 2 × 4 within-subject repeated measure approach was utilized to conduct the research. The sample consisted of 171 Javanese Muslim women, who were selected using accidental sampling. The participants were presented with sequences of vignettes containing manipulated doctors’ profiles based on the three observed aspects of social identity (gender, religion, race), alongside a trust scale specifically designed for assessing trust in doctors. The trust scale comprised four dimensions, namely fidelity (loyalty), competence, honesty, and confidentiality. Data collection was then carried out using the trust scale, and subsequent analysis was performed by employing Bayesian repeated measures ANOVA with JAMOVI 1.6.23.0. The results showed that manipulating the social identity of doctors led to variations in the trust level exhibited by the patients, and this was in support of the proposed alternative hypothesis. Specifically, from the main effect analysis, it was found that gender and religion significantly influenced patients’ trust, while race did not. This implied that patients considered gender and religion as important factors when selecting an Ob-Gyn doctor.